Comparative genome analysis of the SPL gene family reveals novel evolutionary features in maize - Peng,Xiaojian (2019)
Abstract SPLs are plant-specific transcription factors that play important regulatory roles in plant growth and development. Systematic analysis of the SPL family has been performed in numerous plants, such as Arabidopsis, rice, and Populus. However, no comparative analysis has been performed across different species to examine evolutionary features. In this study, we present a comparative analysis of SPLs in different species. The results showed that 84 SPLs of the four species can be divided into six groups according to phylogeny. We found that most of the SPL-containing regions in maize showed extensive conservation with duplicated regions of rice and sorghum. A gene duplication analysis in maize indicated that ZmSPLs showed a significant excess of segmental duplication. The Ka/Ks analysis indicated that 9 out of 18 duplicated pairs in maize experienced positive selection, while SPL gene pairs of rice and sorghum mainly evolved under purifying selection, suggesting novel evolutionary features for ZmSPLs. The 31 ZmSPLs were further analyzed by describing their gene structure, phylogenetic relationships, chromosomal location, and expression, Among the ZmSPLs, 13 were predicated to be targeted by miR156s and involved in drought stress response. These results provide the foundation for future functional analyses of ZmSPLs.